Stacking fault energies of Mn, Co and Nb alloyed austenitic stainless steels - Lu, Song; Hu, Qing-Miao; Johansson, Börje; Vitos, Levente (Acta materialia, 2011)
The alloying effects of Mn, Co and Nb on the stacking fault energy (SFE) of austenitic stainless steels, Fe–Cr–Ni with various Ni contents, are investigated via quantum–mechanical first-principles calculations. In the composition range ( c Cr = 20%, 8 ⩽ c Ni ⩽ 20%, 0 ⩽ c Mn, c Co, c Nb ⩽ 8%, balance Fe) studied here, it is found that Mn always decreases the SFE at 0 K but increases it at room temperature in high-Ni ( c Ni ≳ 16%) alloys. The SFE always decreases with increasing Co content. Niobium increases the SFE significantly in low-Ni alloys; however, this effect is strongly diminished in high-Ni alloys. The SFE-enhancing effect of Ni usually observed in Fe–Cr–Ni alloys is inverted to an SFE-decreasing effect by Nb for c Nb ≳ 3%. The revealed nonlinear composition dependencies are explained in terms of the peculiar magnetic contributions to the total SFE.